Prinsip dan Etika Konsumsi dalam Perspektif Islam (Tinjauan Maqashid Syariah) - Putri Anggraeni; Tati Handayani (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Abstract Consumption Ethics in Islam relates to a set of values ​​and principles to regulate individual behavior in consuming goods and services. However, to achieve maslahah, this consumption ethic must be based on Maqashid Syariah, namely the goals of Islamic Shari'a to be achieved in various aspects of life, one of which is consumption. This article reviews the Principles and Ethics of Consumption from an Islamic perspective from the perspective of maqashid sharia. This research uses a descriptive qualitative method using a literature study approach sourced from relevant documents, magazines, scientific articles, books, and so on. The result of the discussion in this article is that in carrying out wise consumption behavior and in accordance with Islamic principles, it is recommended that consumers always consider the priority of their needs, starting from the most urgent (daruriyah), to the secondary (hajjiyah) and tertiary (tahsiniyah) to ensure that this behavior brings benefits (mashlahah) for the welfare of this world and the hereafter. Keywords: Islamic Perspective, Consumption Ethics, Maqashid Sharia, Maslahah